Changing Pattern of Clinical Illness in Children with Group A Streptococcal Bacteremia - Kim J Burrows; Scott A Halperin; Margaret Swift; Robert Bortolussi (Canadian Journal of Infectious Diseases)
Objective: To test the hypothesis that bacteremia caused by group A streptococci (gas) has become more common and the presentation of the infection more severe in the Izaak Walton Killam Hospital for Children during the past decade.